Bipolar disorder: genetic analysis of the circadian rhythm associated genes and metabolic syndrome - Susmak, Chantay (University of the Free State, 2019)
Bipolar disorder (BD) is a serious, lifelong psychiatric disorder characterised by mood dysregulation. It has been rated as the sixth most debilitating disorder in the world. Comorbidity is often observed, with metabolic syndrome (MetS) as the most prevalent medical comorbidity. The pathophysiology observed between BD and MetS is suggested to be the result of common underlying genetic, environmental and lifestyle risk factors. The circadian rhythm and neurotrophins pathway disruptions play a role in BD and MetS aetiology. The aim of the study was to investigate genetic associations between selected gene variants in these pathways and metabolic risk factors in patients with BD. A case-control design was implemented with 53 BD cases and matched controls. The questionnaire and genotype data were analysed using quantitative and molecular techniques to ensure a thorough comparison of the genetic and environmental components between the two groups investigated. Selected candidate gene polymorphisms have previously been associated with BD, MetS and the circadian rhythm clock. Genotyping of CLOCK (rs1801260), PER3 VNTR (rs57875989), GSK-3β (rs3755557 and rs334558) and BDNF (rs6265) was performed with restriction enzyme digestion and bi-directional sequencing. Statistical analysis was done with the Statistical Analysis System Software. The genotype association with BD and MetS did not deliver statistically significant results. Analysis of multi-locus genotypes, a significant association between CLOCK and GSK-3β rs334558 (p = 0.012) as well as between BDNF and PER3 (p = 0.022) was observed. When comparing the cases with the controls in terms of smoking cigarettes, exercise habits, following a balanced diet, prevalence of hypercholesterolaemia, cardiovascular conditions and diabetes, no differences were observed. A significant difference was observed in the ‘drinking alcohol on a regular basis’ (p = 0.012), where more controls were regular alcohol consumers as compared to the BD cases. With regards to the ‘body mass index’ variable, the majority of BD cases were obese (p = 0.005).
Keywords: Bipolar disorder; Metabolic syndrome; Psychiatric genetics; Genotyping; Dissertation (M.Sc. (Human Molecular Genetics))--University of the Free State, 2019